ANALISIS KEMAMPUAN KONEKSI MATEMATIS DITINJAU DARI KEMANDIRIAN BELAJAR SISWA - Hidayati, Litsa Arfi; Triyana, Evi; Gunawan; Kusno; Jaelani, Anton (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2025)
The ability to make mathematical connections has an important role in the problem-solving process, while learning independence is an affective aspect that supports the learning process. This study aims to analyze the ability of mathematical connections based on learning independence. The research subjects consisted of 35 grade VII students at MTs Minat Cilacap. This study uses a qualitative method with a descriptive approach. Data collection techniques are in the form of mathematical connection ability tests, interviews, and learning independence questionnaires. Based on the questionnaire, students are categorized into high, medium, and low. Each category is taken by one student as a sample with a purposive sampling technique. The material used for the test is Social Arithmetic. Data analysis consists of data reduction, presentation, and conclusion. The results show that students with high independence are able to relate mathematical concepts well and apply them in a variety of situations. Students with moderate independence have sufficient understanding, but still have difficulty in relating concepts thoroughly. Students with low independence experience obstacles in connecting mathematical concepts to other situations. The implications of this study emphasize the importance of implementing innovative learning strategies that can increase learning independence and mathematical connections. Abstrak: Kemampuan koneksi matematis memiliki peran yang penting dalam proses penyelesaian masalah sedangkan kemandirian belajar sebagai aspek afektif yang menunjang proses pembelajaran. Penelitian ini bertujuan untuk menganalisis kemampuan koneksi matematis berdasarkan kemandirian belajar. Subjek penelitian terdiri dari 35 siswa kelas VII di MTs Minat Cilacap. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif. Teknik pengumpulan data berupa tes kemampuan koneksi matematis, wawancara, dan angket kemandirian belajar. Berdasarkan angket, siswa dikategorikan menjadi tinggi, sedang, dan rendah. Setiap kategori diambil masing-masing satu siswa sebagai sampel dengan teknik purposive sampling. Materi yang digunakan untuk tes adalah Aritmatika Sosial. Analisis data terdiri dari reduksi data, penyajian, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa siswa dengan kemandirian tinggi mampu menghubungkan konsep matematika dengan baik dan menerapkannya dalam berbagai situasi. Siswa dengan kemandirian sedang memiliki pemahaman yang cukup, tetapi masih mengalami kesulitan dalam mengaitkan konsep secara menyeluruh. Siswa dengan kemandirian rendah mengalami hambatan dalam menghubungkan konsep matematis dengan situasi lain. Implikasi dari penelitian ini menekankan pentingnya penerapan strategi pembelajaran inovatif yang dapat meningkatkan kemandirian belajar dan koneksi matematis.